Coexistence of Tuberculosis and Lophomoniasis in a Patient With Alzheimer's Disease - Masoud Maboudi; Eissa Soleymani; Elham Sadat Banimostafavi; Shirafkan Kordi; Majidreza Adelani; Zakaria Zakariaei; Mahdi Fakhar (Respirology Case Reports)
ABSTRACT The coexistence of lophomoniasis and tuberculosis (TB), both airborne diseases, is relatively uncommon. Co‐infections like these can complicate treatment strategies due to overlapping symptoms and potential drug interactions. We report a rare case of comorbidity involving two pulmonary diseases, lophomoniasis and TB, in an 82‐year‐old woman with Alzheimer's disease (AD) from northern Iran. Her primary symptoms included weakness, lethargy, dyspnea, sputum production, night sweats, and significant weight loss. Both TB and lophomoniasis can compromise the immune system, potentially worsening the progression or severity of AD by increasing susceptibility to infections or enhancing neuroinflammation. Following the prescription of appropriate drug regimens for both diseases, the patient was discharged from the hospital in stable condition. Overall, it is crucial to consider lophomoniasis in the differential diagnosis of patients with pulmonary tuberculosis, especially in endemic areas where both infections are prevalent, to ensure timely diagnosis and effective management.